MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN SEJARAH MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL SISWA KELAS XI IPS MA MA’ARIF NU 1 KEMRANJEN - Millenia Rahmah Dinia; Darsono (KARMAWIBANGGA: Historical Studies Journal, 2022)
This study aims to determine the increase in student activity in learning History through Audio Visual Learning Media for Class XI IPS MA Ma'arif NU 1 Kemranjen Students.This type of research is Classroom Action Research (CAR). The research subjects were all students of class XI IPS, totaling 28 students. The object of research is the activeness of students by using audio- visual media. Data collection techniqueswere obtained by observation and written tests. Data analysis techniques used are quantitative and qualitative techniques. The results of the research in Cycle I were 35% of students actively asked questions, 39% of students actively answered, 85% of students did assignments, 35% of students chatted and 71% of students remained silent, theresults of Cycle I showed that student activity was in the moderate category. While in Cycle II showed an increase, namely 89% of students actively asked questions, 86% of students actively answered, 92% of students did assignments, 21% of students chatted and 46% of students remained silent, in Cycle II it could be categorized as very high student activity. Thus the use of audiovisual media can increase student activity in history learning for class XI IPS MA Ma'arif NU 1 Kemranjen.